Characteristics of chronic thromboembolic pulmonary hypertension in Ireland. (1st October 2021) - Cullivan, Sarah; McCormack, Ciara; O'Callaghan, Marissa; Kevane, Barry; NiAinle, Fionnuala; McCullagh, Brian; Gaine, Sean P.
Abstract : Chronic thromboembolic pulmonary hypertension (CTEPH) is a rare and under‐recognised complication of acute pulmonary embolism. Information regarding the characteristics of CTEPH in Ireland is limited, and the aim of this retrospective cohort study was to address this knowledge gap. Seventy‐two cases of CTEPH were diagnosed in the National Pulmonary Hypertension Unit (NPHU) in Ireland between 2010 and 2020. This accounted for 6% of all referrals to the unit and translates to an estimated annual incidence of 1.39 per million population (95% confidence interval, 0.33–2.46). The prevalence of diagnosed CTEPH in Ireland in 2020 was estimated at 12.05 per million population (95% CI 9.00–15.10). The average duration of symptoms prior to CTEPH diagnosis was 23 (±22) months. Patients with CTEPH were more likely to be male (n = 40, 56%), older (60 ± 17 years) and have identifiable risk factors for CTEPH (n = 61, 85%) at diagnosis. Regarding treatment, pulmonary hypertension (PH) vasodilator therapy was prescribed in 75% (n = 54) within 12 months of diagnosis, inferior vena cava filters were placed in 24% (n = 17) and 97% (n = 70) of cases were anticoagulated. Pulmonary endarterectomy was performed in 35% (n = 25), balloon pulmonary angioplasty in 6% (n = 4). One‐, three‐ and five‐year survival was 93%, 80% and 65% from the time of diagnosis, and this was significantly better in patients who underwent pulmonary endarterectomy (p = 0.01). This is the first study describing the characteristics of CTEPH in Ireland and highlights suboptimal disease recognition and referral for the assessment for pulmonary endarterectomy.